On the Possibility of Credit Rationing in the Stiglitz-Weiss Model - Arnold, Lutz G.; Riley, John G. (American Economic Review, 2009)
Contrary to what is usually assumed, the expected revenue for lenders as a function of the loan rate cannot be globally hump-shaped in the Stiglitz-Weiss (1981) adverse selection model with a continuum of types. This has important implications. First, if there is credit rationing, there must be at least two equilibrium loan rates. Second, while at the low rate loans are rationed, all those applicants willing to pay the high rate are then served. Numerical analysis shows that unless the joint distribution of risk class and output is rather special, the two loan rate outcome with rationing is unlikely. (JEL D82, G21)